Meleney’s gangrene with superadded aspergillosis: Case report of a rare but fatal surgical complication - Bhatia, Chisel; Dalal, Satish; Beniwal, Jagat Pal; Malwal, Jitendra Singh (Indian Journal of Case Reports, 2018)
Meleney’s ulcer or post-operative synergistic bacterial gangrene is a rare form of necrotizing infection of the abdominal wall which develops following intra-abdominal surgery. If not promptly identified and treated, it can lead to extensive gangrene leading to fatal complications. We report a case of Meleney’s gangrene with superadded aspergillosis which rapidly progressed to gangrene of a large area of the anterior abdominal wall leading to mortality of the patient. We also discuss the difficulties in the management of such cases highlighting the need of early and aggressive debridement besides other measures.